A multilevel analysis of the effects of indoor activities on psychological wellbeing during COVID-19 pandemic - Çetin, Mehmet; Kökalan, Özgür (Anales de Psicología / Annals of Psychology, 2021)
Study aims to analyze the effects of indoor activities such as physical exercise, digital socializing and digital gaming on subjective wellbeing levels of individuals. Given the dynamic nature of the pandemic in order to catch the day level within individual variance (along with between individuals variance) study adapts a multilevel approach where days are nested in people. 1950 day level data are collected from 390 respondent for 5 consecutive days during the first phase of pandemic (when there were strict social isolation policies) in Turkey. Results for partitioning variance components supported the necessity for using a multilevel approach. Findings of analysis conducted though hierarchical linear modeling demonstrated that day level physical activity at home and digital socializing significantly alleviate daily negative affect and positively associates with day level positive affect and happiness levels of respondents. These results were controlled for demographic variables, extraversion and psychological resiliency. Extraversion was negatively and psychological resiliency was positively related to day level negative affect.